Understanding Students’ Perception of Quality Lab Learning Experience: An Analysis from the Qualitative Approach - Chong, Wei Ying; Tan, Gary, Peng-Liang (INTI International University, 2018)
In this exploratory study, a community of inquiry framework was used to investigate students’ perception of the efficacy and quality of lab learning session. It was found that participants valued not only the quality of the equipment, but also the instructor’s timely engagement and reflection. Study participants emphasized the necessity of the instructor’s frequent engagement through various mode of learning methods, such as virtual and face-to-face explanation before class and review after lab session. Participants’ interest in asynchronous instruction was also observed. These findings are in line with previous studies emphasizing the importance of instructor’s engagement in lab sessions. This study contributes to understanding students’ perception of the quality of learning experience in a lab session.